Avalynė Vilniaus Bernardinų bažnyčios freskose - Puškorius, Arūnas (Archaeologia Lituana, 2012)
Kiekvienas naujas Lietuvoje surastas rašytinis ar ikonografinis šaltinis netrukus būna pastebėtas įvairių sričių tyrėjų. Jis patenka į mokslinę apyvartą, tampa publikacijų ir įvairių didesnės apimties darbų tyrimų objektu. Nauji surasti ir restauruoti vaizduojamojo meno objektai – sienų tapyba monumentaliuose kultūros paminkluose – yra neįkainojamos vertės mokslinio pažinimo šaltinis. Jis tiesiogiai liudija apie čia dirbusius amatininkus, konkretaus laikotarpio žmonių mentalitetą, estetinį ir pasaulio suvokimą. Šie objektai tiriami ir daug žemiškesniais aspektais: analizuojamos piešimo technologijos ir technikos, pigmentai, pagal poreikį atliekami kiti medžiagotyriniai darbai. Taigi sienų freskos yra puikus senųjų laikų įvairiapusio pažinimo objektas. ... SHOES IN THE WALL PAINTING AT THE VILNIUS BERNARDINE CHURCH Arūnas Puškorius Summary The interior wall-painting on the northern wall at the Vilnius St. Franciscus and St. Bernardine Church (Bernardine Church) is very valuable and is the only example of a well preserved subject-painting of the Gothic period in Lithuania. The interior of the Bernardine Church is considered to have been painted after the reconstruction early in the 16th century (not later than 1521). Its common stylistics is highly influenced by the German graphics. Without any doubt, a lot of figures have been transferred from the illustrated book “Prayers and Morals” composed by Stephan Fridolino, an Observant German Franciscan priest. The book was published in 1491 by Anton Koberger in Nuremberg. Nevertheless, the decoration program on the wall of the Bernardine Church is specific. The purpose of this study was to discuss and identify the shoes that are painted in this wall-painting in the context of the different social strata of first half of the 16th century, and to compare these painted shoes with the Vilnius archaeological finds and other analogues in Europe. ...